A surface acoustic wave (SAW)-enhanced grating-coupling phase-interrogation surface plasmon resonance (SPR) microfluidic biosensor. Issue 7 (2nd March 2016) - Sonato, A.; Agostini, M.; Ruffato, G.; Gazzola, E.; Liuni, D.; Greco, G.; Travagliati, M.; Cecchini, M.; Romanato, F.
Abstract : A novel, surface plasmon resonance phase-interrogation based microfluidic biosensor in which surface acoustic wave-driven mixing accelerates molecule binding kinetics up to 84% of the reaction time is presented. Abstract : A surface acoustic wave (SAW)-enhanced, surface plasmon resonance (SPR) microfluidic biosensor in which SAW-induced mixing and phase-interrogation grating-coupling SPR are combined in a single lithium niobate lab-on-a-chip is demonstrated. Thiol-polyethylene glycol adsorption and avidin/biotin binding kinetics were monitored by exploiting the high sensitivity of grating-coupling SPR under azimuthal control. A time saturation binding kinetics reduction of 82% and 24% for polyethylene and avidin adsorption was obtained, respectively, due to the fluid mixing enhancement by means of the SAW-generated chaotic advection. These results represent the first implementation of a nanostructured SAW–SPR microfluidic biochip capable of significantly improving the molecule binding kinetics on a single, portable device. In addition, the biochip here proposed is suitable for a great variety of biosensing applications.